Abundant expression of mTOR kinase in salivary gland tumors – potentials as therapy target?. (25th March 2013) - Clauditz, Till Sebastian; Gontarewicz, Artur; Bokemeyer, Carsten; Sauter, Guido; Knecht, Rainald; Münscher, Adrian; Wilczak, Waldemar
Abstract : Background: Salivary gland tumors constitute 3–6% of all head and neck neoplasms in adults. Because of limited advances made in the treatment of metastatic disease, the more important is the role of new therapeutic strategies, including molecular therapy. The mammalian target of rapamycin (mTOR) has recently been established as a therapeutic target for several drugs. Material: Evaluation of phospho‐mTOR as a possible therapy target by patients with salivary gland tumors. Immunohistochemical semi‐quantitative analyses of the expression of phospho‐mTOR(Ser2448) were processed on a tissue microarray containing samples from more than 900 patients. For statistical analysis, contingency table and chi‐squared test (likelihood) were used. Results: We observed at least weak phospho‐mTOR expression in 25.6–41.2% of all 4 histological adenoma and in 36.8–61.6% of all 11 histological carcinoma subtypes analyzed. No association was seen between phospho‐mTOR expression and tumor grade in mucoepidermoid carcinomas. Conclusion: In conjunction with literature data providing the evidence for a functional role of mTOR in salivary gland tumors, we conclude that treatment with mTOR‐antagonists might potentially also be efficient in wide variety of salivary gland carcinomas.